The Effectiveness of Blue-Light-Emitting Glasses in Security Guards Exposed to Night Shift Work on Work-Related and General Fatigue: A Randomised Controlled Cross-Over Study - Pieter H. Helmhout; Stella Timmerman; Alwin van Drongelen; Eric W. P. Bakker (Clocks & Sleep, 2022)
This study aimed to evaluate the effectiveness of glasses that emit blue light in reducing the need for recovery, general fatigue, and stress levels in security guards who work night shifts. Light manipulation is seen as a promising strategy to mitigate complaints related to shift work, such as sleepiness and impaired cognitive performance. In a randomized controlled cross-over study design, 86 Dutch security guards used light-emitting glasses (exposure duration: 30 min) during night shifts in a five week period versus a five week control period without glasses. Measurements (Need for Recovery Scale; Checklist Individual Strength; stress level assessed by a fitness tracker) were performed at baseline, at five weeks, and again at 11 weeks. The chronotype was measured at baseline as a potential covariate. A mixed model for repeated measure analyses showed no significant reduction in the need for recovery, nor a reduction in general fatigue scores, during the intervention period. Paired Samples T-Test analyses showed no significant changes in stress levels for the intervention period. Conclusively, blue light exposure using light-emitting glasses for security guards during night shifts showed no directly measurable effect on the reduced need for recovery, overall fatigue, and stress levels.